Primary melanoma of oral mucosa: A case report and review of literature - Bhullar, Raman Preet Kaur (Medknow Publications & Media Pvt Ltd, 2012)
Primary oral melanoma is a rare neoplasm of melanocytic origin, accounting for 0.5% of all oral malignancies. The “chameleonic” presentation of a mainly asymptomatic condition, rarity of this lesion, poor prognosis, and the necessity of a highly specialized treatment are factors that should be seriously considered by the involved health provider. Here is a case report presenting a malignant melanoma of oral mucosa in 48-year-old male patient on maxillary gingiva. The lesion was removed by partial maxillectomy and patient is disease free after 11 months of regular followup. This case provides an example of how dental clinicians play a major role in the identification of pigmented lesions of oral cavity and also emphasize on the fact that any pigmented lesion detected in the oral cavity may exhibit potential growth and should be submitted to biopsy to exclude malignancy.